Resolving mixed mechanisms of protein subdiffusion at the T cell plasma membrane - Yonatan Golan (Nature Portfolio, 2017)
Membrane protein diffusion is affected by distinct mechanisms such as molecular crowding and medium elasticity. Here the authors present an analytical approach to analyse single particle trajectories and distinguish mixed subdiffusive processes affecting membrane protein mobility in living cells.